HIBAH KEPADA LEMBAGA YUDIKATIF DAN KEPATUHAN PEMERINTAH DAERAH MEMULIHKAN KERUGIAN KEUANGAN DAERAH - Arief Adrian (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2021)
Many local governments have discretionary spending (such as grants) on judicatory institutions such as police, attorney, and court. The grant potentially creates a bond between local government and judicatory institutions, reduces the objectivity of law enforcement, and hence affects regulatory compliance. This study attempts to identify whether or not grants on regional judicatory institutions are correlated with local government compliance in recovering regional finance loss. Using 2,426 observations from 508 districts in Indonesia from 2014-2018, we find that grants on judicatory institutions are negatively correlated with local government compliance in recovering the regional financial loss. This study calls for improvement in regulations in grant spending to improve the governance of the local government budget.